Uji Kesesuaian Generator Tabung Sinar-X dan Automatic Exposure Control (AEC) pada Mamografi Digital di RSD Mangusada Badung - Johanes J. Silalahi; Gusti Ngurah Sutapa; I Nyoman Pranditayana; I Nengah Sandi; I Gde Antha Kasmawan; Ni Putu Yuni Nurmalasari (Kappa Journal, 2024)
This study focuses on evaluating the quality and performance of the digital mammography system at Mangusada Badung Regional Hospital (RSD) in an effort to prevent and early detect breast cancer. With the prevalence and mortality rate of breast cancer continuing to increase, early detection is important. Digital mammography has an important role in this early detection. This study aims to evaluate the performance of digital mammography at Radiology Installation Mangusada Badung through a series of tests. generator and x-ray tube suitability test and automatic exposure control (AEC). The results showed conformity tests on voltage accuracy (maximum error 0.8%), linearity (CL 0.01), reproducibility (radiation output CV 0.001, peak voltage CV 0.003), emergency timer (stops at 0 mAs), tracking (% patient thickness % exposure index error 7.9%, voltage exposure index error 6%), AEC (voltage CV 0.000, current time CV 0.000), exposure time (large focus t 0.87 seconds, small focus t 1.21 seconds). The test results show that the digital mammography system meets the conformity test criteria in accordance with PERKA BAPETEN no. 2 of 2022. This provides confidence that the device meets the established quality standards. With this fulfillment, it is expected that the accuracy of diagnosis can be improved and the risk of errors in early detection of breast cancer can be reduced. Therefore, the digital mammography system at RSD Mangusada Badung is expected to be.